(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Metabolic syndrome (MetS) is a multifaceted syndrome comprises a cluster of metabolic abnormalities including hypertension, central obesity, insulin resistance, dyslipidemia, and is strongly associated with developing diabetes mellitus and cardiovascular diseases. Prevalence of MetS differs in different ethnic population by using different definition. Objectives: To determine the prevalence of the MetS and its component risk factors among Border Guard Bangladesh (BGB) personnel working in Chattagram Hill Tract (CHT). Materials & Methods: This descriptive cross-sectional study was conducted from October 2016 to February 2018 among 1455 male BGB personnel aged between 40 to 59 years and working in CHT of Bangladesh. Study subjects were selected at BGB hospital, Guimara, Khagrachari. The new International Diabetes Federation (IDF) guidelines were used to identify MetS. Detail history, clinical examination, anthropometry and blood pressure (BP) were measured and fasting plasma glucose (FPG) and lipid profile were assessed. Results: Among the 1455 respondents’ BMI, waist circumference, systolic and diastolic BP were found more than normal in 34.1, 37.7, 16.4% and 12.3% respectively. Biochemical parameters including FPG, TC, TG, and LDL-C was raised in 28.7%, 49.8%, 52.2% and 37.7% of respondents respectively. HDL-C was found decreased in 26.9% respondents. Age wise prevalence of MetS for age group 40-44, 45-49, 50-54 and 55- 59 years were found 21.3%, 21.7%, 24.1% and 26.1% of the respondents respectively. The overall prevalence of MetS was found 22.4%. Conclusion: The prevalence of the MetS in BGB personnel was found 22.4%. Appropriate measure should be taken to lower the MetS cases. Journal of Armed Forces Medical College Bangladesh Vol.14 (2) 2018: 97-100